Innovations, adaptations, and accelerations in the delivery of HIV services during COVID-19. Issue 12 (December 2022) - Murphy, Eamonn; Doherty, Meg; El Sadr, Wafaa; Zaidi, Irum; Kamarazulman, Adeeba; Crowley, Siobhan; Anam, Florence Riako; Modi, Chinmay; Castellanos, Erika; Garner, Alex; McCulloch, Neil; Taslim, Aditia; et al.
Summary: During 2020, the COVID-19 pandemic disrupted the delivery of HIV prevention and treatment services globally. To mitigate the negative consequences of the pandemic, service providers and communities adapted and accelerated an array of HIV interventions to meet the needs of people living with HIV and people at risk of acquiring HIV in diverse geographical and epidemiological settings. As a result of these adaptations, services such as HIV treatment showed programmatic resilience and remained relatively stable in 2020 and into the first half of 2021. To review lessons learned and suggest which novel approaches to sustain, UNAIDS convened a virtual consultation on Feb 1–2, 2022, which was attended by a range of stakeholders from different areas of global HIV response.